Tata Laksana Komprehensif Terkini Penanganan Re-Emergensi Hand, Foot, and Mouth Disease (HFMD) di Indonesia: Tinjauan Lingkup: Tinjauan Pustaka - Muhammad Alifian Remifta Putra (Cermin Dunia Kedokteran, 2024)
Hand, foot, and mouth disease (HFMD) is an exanthematous disease with the main manifestation of a maculopapular rash eruption on the hands, feet, and mouth accompanied by fever with potentially serious complications in children under five-years-old. Indonesia has a recurring cycle of HFMD outbreaks, making it a re-emergent disease. The author conducted a systematic search in three databases, including Pubmed, Wiley Online Library, and Science Direct, with the keywords "hand, foot, and mouth disease,"enterovirus", and "therapy," published from 2000 until 2023. A total of 791 studies were included in the analysis, and their quality was assessed using the Newcastle-Ottawa Scale. The currently available comprehensive HFMD management includes prevention, therapy, and complication management. Current research has not succeeded in uncovering a definitive treatment; thus, management focused on symptomatics, followed by isolation with good oral and skin care. In severe cases, available options include antiviral therapy and intravenous immunoglobulin, along with respiratory and blood circulation system support. Research has shown that the inactivated Enterovirus A71 (EV-A71) vaccine is the most effective and cost-effective option. However, the evolution of enterovirus epidemiology caused one agent intervention that will be inadequate in the future; thus, developing definitive treatments and effective multivalent vaccines is essential.